Verification of Operation Modes of Designed LLC Resonant Converter - Spanik, Pavol; Kandrac, Jozef; Frivaldsky, Michal; Drgona, Peter (Communications - Scientific letters of the University of Zilina, 2011)
This paper describes the design of the LLC resonant converter, which is done by means of fundamental harmonic approximation (FHA). Output power of proposed converter is 1kW with output voltage 48 V at switching frequency of 500 kHz. Performance of converter at different operational conditions was verified through simulation analysis by utilization of OrCAD PSpice software. The simulation results of multiple parametrical experiments were obtained and consequently evaluated into graphical interpretation of efficiency of proposed converter.